Monolithic heterojunction quasi-solid-state battery electrolytes based on thermodynamically immiscible dual phases. Issue 2 (26th September 2018) - Cho, Sung-Ju; Jung, Gwan Yeong; Kim, Su Hwan; Jang, Minchul; Yang, Doo-Kyung; Kwak, Sang Kyu; Lee, Sang-Young
Abstract : Monolithic heterojunction quasi-solid-state battery electrolytes (MH-QEs) based on thermodynamically immiscible dual phases are presented as an electrode-customized multifunctional electrolyte. Abstract : Traditional single-phase electrolytes, which are widely used in current state-of-the-art rechargeable batteries, have difficulties simultaneously fulfilling different chemical/electrochemical requirements of anodes and cathodes. Here, we demonstrate a new class of monolithic heterojunction quasi-solid-state electrolytes (MH-QEs) based on thermodynamically immiscible dual phases. As a proof-of-concept of the MH-QEs, their application to lithium–sulfur batteries is explored. Driven by combined effects of structural uniqueness and thermodynamic immiscibility, the electrode-customized MH-QEs provide exceptional electrochemical performance that lies far beyond those accessible with conventional battery electrolytes.